Socioeconomic and health disparities in adults diagnosed with type 1 diabetes mellitus before age 18: insights from the Italian PASSI surveillance system - Zamagni, Giulia; Minardi, Valentina; Masocco, Maria; Asta, Federica; Candido, Riccardo; Tornese, Gianluca; Bresciani, Giulia; Manfredini, Valentina; Frattolin, Elena; Carletti, Claudia Veronica; Germano, Daniela; Maurel, Eleonora; et al. (Frontiers in Public Health, 2025)
BackgroundType 1 diabetes mellitus is a lifelong condition with consequences that extend well beyond glycaemic control, often impacting individuals' socioeconomic status and overall quality of life. In Italy, the broader effects of early-onset type 1 diabetes on social and health-related outcomes have been insufficiently investigated. Therefore, this study aimed to investigate the socioeconomic impacts of type 1 diabetes among adults diagnosed with the condition before age 18.MethodsUsing data from the Italian Behavioral Risk Factor Surveillance System (PASSI) collected between 2011 and 2018 and in 2023, we analyzed key outcomes in adults aged 18–50 who were diagnosed with type 1 diabetes before age 18 and were on insulin therapy. Each case was matched by age and sex to two non-diabetic controls. Descriptive statistics and multivariable logistic regression were used to compare key indicators.ResultsOur sample included 993 participants (331 cases and 662 controls). Cases had significantly higher odds of being unemployed [OR = 1.57 (1.20–2.07)], experiencing severe financial difficulties [OR = 1.81 (1.05–3.13)], and reporting poor self-rated health [OR = 6.64 (2.53–17.43)]. Cases also had an increased likelihood of reporting physical impairment for 1–13 days [OR = 1.91 (1.30–2.81)] and ≥14 days [OR = 2.95 (1.54–5.65)], mental health impairment for 1–13 days [OR = 2.16 (1.46–3.19)], and daily activity limitations for 1–13 days [OR = 1.73 (1.06–2.82)].ConclusionsThese findings highlight the multifaceted burden of type 1 diabetes and the need for integrated approaches to care that address not only clinical but also socioeconomic and psychosocial dimensions of the disease.